2021
DOI: 10.29132/ijpas.987436
|View full text |Cite
|
Sign up to set email alerts
|

Enerji Depolamalı Bir Boruda Nanoakışkan Kullanımının Isıl Performansa Etkisinin Sayısal Olarak İncelenmesi

Abstract: Teknolojideki gelişmeler göz önüne alındığında, yüksek verimli elektronik cihazlardan beklenen verimlilik ve güvenirliğe ulaşmak için iyi bir termal performansa sahip yeni yaklaşımlar ve soğutuculara ihtiyaç duyulmaktadır. Bu çalışmada aynı hidrolik çapa, kanal uzunluğuna ve kesit geometrisine sahip alüminyum boru kullanılmıştır. Sistemin ısı transfer hızını arttırmak için; boru içerisinde su, %1 ve %2 derişimlerine sahip Al2O3/su nanoakışkanları, boru dış yüzeyinde ise 5mm kalınlığında RT25HC faz değiştiren m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the experiment, which is carried out with only water without mixing, the temperature of the water increased from 29.3 o C to 41.8 o C within 90 minutes, resulting in a temperature increase of 12.5 o C. According to the results obtained, it is determined that the pure water + aluminum oxide mixture heated 59.52% more than the normal unmixed water. In another study, it is observed that the pure water + aluminum oxide mixture is 61.1% more efficient than the normal unmixed water in the yield value calculated according to the ASHRAE 93-2003 standard [24].…”
Section: The Comparison Of Mixtures Made With Nanofluidsmentioning
confidence: 97%
“…In the experiment, which is carried out with only water without mixing, the temperature of the water increased from 29.3 o C to 41.8 o C within 90 minutes, resulting in a temperature increase of 12.5 o C. According to the results obtained, it is determined that the pure water + aluminum oxide mixture heated 59.52% more than the normal unmixed water. In another study, it is observed that the pure water + aluminum oxide mixture is 61.1% more efficient than the normal unmixed water in the yield value calculated according to the ASHRAE 93-2003 standard [24].…”
Section: The Comparison Of Mixtures Made With Nanofluidsmentioning
confidence: 97%